APPRAISAL OF CAROTID COLOUR DUPLEX ULTRASOUND IN ISCHEMIC STROKE - Khan, Atta Muhammad; Taqweem, Muhammad Amjad; Ali, Murad (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the diagnostic value of Carotid Colour Duplex Ultrasound in Ischemic Stroke patients. Material and Methods: This hospital based non-invasive descriptive study was conducted on patients of ischemic stroke at Lady Reading Hopistal Peshawar from January to August, 2008. Carotid Colour Duplex Ultrasound was performed on each patient in Radiology Department. Patients were selected by nonprobability convenient sampling method after obtaining an informed consent. Patients less than 15 years of age and having haemorrhagic stroke on C.T Scan were excluded from the study. Results: Out of 100 diagnosed cases of ischemic stroke there were 46% males and 54% females, with age range form 21 to 103 years and mean age was 60.34 years. On carotid duplex ultrasound, carotid stenosis was found in 31% patients. Out of these 31 patients, right carotid artery was involved in 16 (51.62%) and left in 13 (41.94%) patients. Normal blood flow was seen in 10 (32.26%) patients, between 20-40 cms/sec in 13 (41.94%) and below 20 cms/sec in 8 (25.81%) patients. High-grade degree of stenosis was found in 17 (54.84%), moderate in 8 (25.81%) and mild in 6 (19.35%) patients. Calcified type of plaque was noted in 18 (58.06%) and soft in 13 (41.94%) patients. Conclusion: Carotid Colour duplex ultrasound is non-invasive, inexpensive technique, and can be used to assess the presence and severity of carotid artery stenosis. It can provide an efficient, accurate and reliable method for clinical evaluation and quantification of carotid blood flow volumes in ischemic stroke patients.